Dormancy performance of Brachiaria brizantha seeds submitted to thermal and chemical treatments - Martins, Leila; Silva, Walter Rodrigues da (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this research was to study the effects of thermal and chemical treatments on Brachiaria brizantha cv. Marandu seeds, in relation to dormancy. Seeds showing dormancy indices superior to 25%, and physical purity above 98%, were submitted to temperatures of 40, 55, 70 and 85°C for periods of 5, 10 and 15 hours, to immersion in sulphuric acid (98%, 36N) for 15 minutes, and to germination on substrate moistened with an aqueous solution of potassium nitrate 0,2%. At the beginning and at the end of storage for nine months under uncontrolled laboratory conditions, seeds were evaluated in relation to germination, tetrazolium viability, damages on lemma and palea, first count of germination, seedling shoot length, seedling emergence and speed of emergence index. Thermal specific treatments reduce the dormancy index of seeds; heating at 70°C for 10 and 15 hours, besides reducing the dormancy index, also causes immediate positive effects on the performance of seeds without producing latent physiological deterioration. Application of 85°C and immersion in sulphuric acid, although causing reduction in dormancy and immediate positive effects on performance of seeds, also promote latent physiological deterioration.